FOREIGN EXPERIENCE OF FINANCIAL SUPPORT OF AGRICULTURAL ENTERPRISES - Dustova , Mukhayyo; Ochilova , Sevara (THE INNOVATION ECONOMY, 2023)
This article examines the foreign experience and best practices in providing financial support to agricultural enterprises. It explores various financial mechanisms, policies, and initiatives implemented in different countries to promote the growth and sustainability of the agricultural sector. The article discusses the role of government funding, subsidies, grants, loans, and investment programs in supporting agricultural enterprises. It also analyzes the outcomes and impacts of these financial support measures on agricultural productivity, innovation, rural development, and economic growth. The article aims to provide insights and lessons that can inform policymakers and stakeholders in developing effective financial support strategies for agricultural enterprises.